The scientist and the scribe - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Misunderstandings sometimes fly about between scientists and journalists: the former provide indigestible information, it is said, and the latter misrepresent. Yet, like mealie porridge and a sauce, they need each other, and so, in mid-October 2002,...